Enhancing Patient Engagement in HTA: Using Consensus Research to Overcome PICO Scoping Challenges Under the EU HTAR - Emanuele Arcà; Adele Barlassina; Adaeze Eze; Valentina Strammiello (Journal of Market Access & Health Policy)
The evolving landscape of Health Technology Assessment (HTA) in Europe, shaped by the implementation of the new EU HTA Regulation (HTAR), places an emphasis on engaging all stakeholders, including patients, in collaborative evidence generation. Yet integrating patients’ perspectives into critical processes like PICO scoping remains a challenge, with concerns around subjectivity, representativeness, and methodological robustness. This opinion paper examines the complexities of patient engagement in HTA, highlighting both the opportunities for patients to make meaningful contributions and the barriers that stand in the way. We propose a framework that employes the Delphi panel methodology to (1) foster scientific validity and increase transparency in patient contributions, (2) establish a structured and consistent patient engagement framework, and (3) and understand European patients’ perspectives while promoting collaboration among EU countries. By facilitating iterative feedback and fostering agreement among diverse groups of patients and caregivers contributing with their expertise, consensus methods like Delphi panels can help refine PICO criteria, align diverse stakeholders’ expectations, and increase the relevance of HTA outcomes. A study is now underway to evaluate the feasibility and value of using the modified Delphi panel methodology for patient engagement in PICO scoping. The authors propose that embracing patient engagement through carefully designed consensus frameworks could enhance the legitimacy and completeness of HTA processes, driving more patient-centered decision making across Europe.